Analyzing historical photographs from the British Colonial period : The Federal Conference Group, Kuala Kangsar, 1897 - Raziq Abdul Samat; Azahar Harun; Mohamed Razeef Abd Razak; Khairul Azril Ismail; Shafirah Shaari (Institute of the Malay World and Civilization, Universiti Kebangsaan Malaysia, 2022)
Historically, photography has been used to document historical events; however, these images typically feature simply a brief synopsis of the year, the event’s name, and the individuals depicted. Each subject in a photograph is a representation of the time period depicted and must be identified. As such, this presentation will analyse historical pictures through the lens of a Critical Visual Methodology (CVM). Objectively, this study will identify the visual features and analyse the photograph’s composition. The study is based on a photograph of the inaugural Durbar Conference entitled Federal Conference Group, Kuala Kangsar, 1897 by G R Lambert & Co. The visual study reveals that each row of the group portrait indicates their status and hierarchy, beginning with the Sultan and ending with the British officer, aristocrat, and soldier.